Cohesive Devices used in Students’ Argumentative Essay; A Discourse Analysis - Ifoni Ludji; Erny S.N. Hambandima; Yuningsih Nita Christiani (Universitas Hamzanwadi, 2022)
The cohesive devices are one of the important aspects of academic writing that has been recognized as a fundamental characteristic of good writing. The aims of this study are to find out the types of cohesive devices used by students and to identify the error of using cohesive devices when composing an argumentative text. This study recruited ten students from the fifth semester of the English language program in the 2021/2022 academic year. The research approach used in this study was descriptive qualitative. This entire data were analyzed by identifying the kind of cohesive devices used and also errors of using the cohesive devices. Based on the documentary results of the student's argumentative essay, it indicated that the students used only three types of cohesive devices as a reference, conjunctions, and substitutions. While there are two types of errors revealed in student essays of using cohesive devices, namely; references and conjunctions. The types of references included personal references, such as; they, them, and it, as well as demonstrative references, such as; that, those, and these. Furthermore, there are errors with additive conjunctions such as the using of and or. The Errors in causal conjunctions, such as; using the conjunctions so and because. The students often used the cohesive devices inefficiently, incorrectly, or excessively. In other words, the sentences are not linked correctly and properly. It seems that students cannot use cohesive devices in writing because they do not understand how to use them properly.